Preparation method of green and environment-friendly sodium ion battery hard carbon negative electrode material

Through pre-carbonization, particle size control, precursor material preparation and high-temperature carbon coating, the problem of impurities in the hard carbon negative electrode materials of sodium ion battery is solved, and a green and environmentally friendly preparation process is realized, which improves electrochemical performance and processing performance. , reduces production costs.

CN119252870AActive Publication Date: 2025-01-03SHENZHEN JANAENERGY TECH CO LTD

Patent Information

Application Number
CN202411616059.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-03
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The remaining metal impurities and alkaline impurities in the hard carbon anode materials of existing sodium ion batteries affect the irreversible decomposition of the battery's electronic conductivity, pH and catalytic electrolyte, resulting in poor circulation ratio and processability, and traditional strong acid purification The method is costly and the environmental pollution is severe.

Method used

Using pre-carbonization, particle size control, precursor material preparation, high-temperature sintering and high-temperature carbon coating, metal impurities are removed through sand grinding and acid treatment, to form hard carbon materials with neutral pH, and carbon coating is carried out at high temperature. To improve material purity and electrochemical properties.

Benefits of technology

The preparation of hard carbon anode material for sodium ion batteries is realized, which reduces production costs, improves electrochemical performance and processing performance, avoids environmental pollution, and improves the first-week efficiency and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a green and environment-friendly sodium ion battery hard carbon negative electrode material preparation method, which comprises: S1, pre-carbonization: pre-carbonizing a biomass raw material under a protective atmosphere to obtain a pre-carbonized material; s2, granularity control treatment: crushing and refining the pre-carbonized material obtained in the step S1 to obtain a refined pre-carbonized material; s3, preparation of a precursor material: stirring and dispersing the refined pre-carbonized material obtained in the step S2, an acid solution and deionized water to form precursor slurry, carrying out temperature-controlled sanding, and then carrying out solid-liquid separation, water washing and drying to obtain the precursor material; s4, high-temperature sintering: performing high-temperature carbonization on the precursor material obtained in the step S3 in a protective atmosphere to obtain a purified hard carbon material; and S5, high-temperature carbon coating: carrying out high-temperature carbon coating on the surface of the purified hard carbon material obtained in the step S4 to obtain the surface-coated hard carbon negative electrode material. The preparation method has the characteristics of greenness, environmental protection, excellent electrochemical performance and good processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion electrodes have the advantages of abundant raw material resources, low manufacturing cost, good low-temperature performance, excellent safety performance and rate performance, and are a powerful supplement to lithium iron phosphate batteries and an excellent solution to replace lead-acid batteries. Among the many sodium-ion battery negative electrode technology routes, hard carbon negative electrode materials have the advantages of a wide range of raw material sources, low cost, low working potential, high capacity, and good cycle stability, and are considered to be the best solution for the commercialization of sodium-ion batteries.

[0003] At present, the cost and large-scale application of hard carbon materials are restricted by the supply of hard carbon raw materials. The available carbon sources include chemical raw materials such as biomass and resin, and fossil raw materials such as coal and asphalt. Among them, biomass raw materials have the advantages of wide sources, low prices, sufficient supply, and renewability, and are considered to be the ideal choice for large-scale production of hard carbon.

[0004] The main components of biomass raw materials are carbon-containing organic matter, which is formed into carbon materials by high-temperature cracking. However, biomass raw materials naturally contain metals required for biomass growth, such as Fe, Na, K, Mg, Ca, etc. The remaining impurities (ash) in hard carbon materials will lead to problems such as reduced electronic conductivity of the material, alkaline pH, irreversible decomposition of catalytic electrolyte, etc., affecting the battery's cycle rate, processability and other performance.

[0005] Impurities in hard carbon materials exist in the form of metal oxides and metal salts, which are generally removed by purification using strong acids in a reactor at high temperatures. However, this method requires the use of large amounts of acid, is expensive, and causes serious environmental pollution, making it unsuitable for commercial production applications. Summary of the invention

[0006] The purpose of the present invention is to provide a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, which has the characteristics of being green and environmentally friendly, having excellent electrochemical properties and good processability.

[0007] The present invention can be implemented by the following technical solutions: The present invention discloses a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Pre-carbonization: pre-carbonizing the biomass raw material under a protective atmosphere to obtain a pre-carbonized material; S2, particle size control processing: crushing and refining the pre-carbonized material obtained in step S1 to obtain refined pre-carbonized material; S3, preparation of precursor material: the refined pre-carbonized material obtained in step S2, acid solution and deionized water are stirred and dispersed to form a precursor slurry, and the solid-liquid separation, water washing and drying are performed after temperature-controlled sand milling to obtain a precursor material; the acid solution is hydrochloric acid; the amount of the acid solution added is 1-20wt.% of the mass of the pre-carbonized material, the pH of the precursor slurry is 4-6; the solid content of the precursor slurry is 15-30%; S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under a protective atmosphere to obtain a purified hard carbon material; S5, high temperature carbon coating: the surface of the purified hard carbon material obtained in step S4 is subjected to high temperature carbon coating to obtain a surface-coated hard carbon negative electrode material.

[0008] In step S3 of the present invention, water-insoluble or acid-soluble impurities, such as silicates, cannot be dissolved into an aqueous solution. Such impurities will not dissolve in the electrolyte after being prepared into electrodes during the subsequent slurry coating process, and will not have an adverse effect on the processing process and battery performance. The amount of acid added and the pH of the slurry affect the effect of the present invention: if the amount of hydrochloric acid added is too little, the effect of the present invention cannot be achieved; if the amount of hydrochloric acid added is too high, the production equipment will be increased, and the too low pH will corrode the equipment, which is not conducive to actual production applications. The solid content of the slurry affects the effect of the present invention: if the solid content of the slurry is low, the output of a single sand grinding is low, pushing up the production cost; if the solid content of the slurry is high, it is not conducive to the dissolution of metal impurities. The solid content of the slurry affects the effect of the present invention.

[0009] Furthermore, in step S3, the sand milling temperature is 30-80°C. During the sand milling process, the slurry will gradually heat up due to the grinding heat, so cooling water is required to control the sand mill temperature at an appropriate value. On the one hand, high temperature can promote the reaction between hydrochloric acid and metal impurities in the carbon material and promote the dissolution of metal impurities; on the other hand, if the temperature is too high and exceeds the maintenance temperature of the equipment, it will affect the service life of the equipment; the sand milling time is 1-6h, and the D50 of the precursor material is ground to 3-10μm.

[0010] Furthermore, in step S3, the precursor material is washed with water until the pH value is 6-7; the solid-liquid separation method is centrifugation and / or filter pressing to separate the metal impurities dissolved in the aqueous solution from the hard carbon material, and the water washing process further washes away the water-soluble impurities on the surface of the hard carbon material; through acid dissolution and water system, part of the metal impurities are converted into chloride salts, and the boiling point of chloride salts is usually low; the drying method is one or more of blast oven drying, flash drying, vacuum oven drying, tunnel drying furnace, double cone dryer, belt dryer, and rake dryer.

[0011] Furthermore, in step S5, the high-temperature carbon coating method is one or more of chemical vapor deposition (CVD), liquid phase coating and high-temperature solid phase coating; the raw material of the high-temperature carbon coating is a carbon source free of metal impurities, and the carbon source is one or more of asphalt, phenolic resin, PVP, PVA, dopamine, glucose, PAA, citric acid, phenol, benzene, toluene, and acetylene.

[0012] Furthermore, in step S5, the amount of the carbon layer in the high-temperature coated carbon is 0.5-5wt.% of the weight of the hard carbon material. If the coated carbon layer is too thin, a uniform and complete coating layer cannot be formed on the surface of the hard carbon material; if the amount of the coated carbon is too much, the production cost is increased; the heating rate is 1-10 ℃ / min, the carbonization temperature is 600-1100 ℃, and the carbonization time is 1-3 h.

[0013] Specifically, the carbon layer coated on the surface of the hard carbon material is pure carbon, and a uniform and dense carbon layer is formed on the surface of the hard carbon material. On the one hand, it isolates the internal biomass carbon material from contact with the electrolyte, further avoiding the adverse effects of impurities in the biomass hard carbon material on the battery performance; on the other hand, the coating layer can reduce the specific surface area of ​​the biomass hard carbon material, reduce the contact area between the material surface and the electrolyte, and improve the first-week efficiency, cycle and storage performance of the battery.

[0014] Furthermore, in step S4, the conditions for high-temperature carbonization are: a heating rate of 0.5-10 ℃ / min, a carbonization temperature of 1100-1500 ℃, and a carbonization time of 2-5 h; during the high-temperature carbonization process, part of the chloride salts that have not been removed from the material are vaporized under the action of high temperature and carried away from the material in the inert gas flow, thereby achieving the purpose of further purifying the hard carbon material.

[0015] Furthermore, in step S2, the pre-carbonized material is pulverized to a D50 of 5-20 μm, and the pulverization method is one or more of jaw crusher, roller crusher, air flow mill, mechanical mill, ball mill, Raymond mill, and stirred mill.

[0016] Furthermore, in step S1, the carbonization conditions are: a heating rate of 1-20°C / min, a carbonization temperature of 300-900°C, and a carbonization time of 1-5 h.

[0017] Specifically, the carbonization conditions will affect the effect of the present invention: in this process, the organic matter in the biomass is gradually cracked and carbonized, and the metal elements are converted into inorganic salts. If the carbonization temperature is low, the metal elements cannot be completely converted into inorganic salts, and it is difficult to be removed by subsequent processes; if the carbonization temperature is too high, the pores of the carbon material collapse and close under the action of high temperature, causing the inorganic salts to be wrapped inside the carbon material, so it is difficult to remove.

[0018] Furthermore, in step S1, the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal.

[0019] Further, in steps S1 / S4 and S5, the protective atmosphere is nitrogen and / or argon.

[0020] The present invention provides a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, which has the following beneficial effects: First, it is green and environmentally friendly. The invention uses the intense friction and impact between sand grinding media and material particles, as well as between material particles to promote the dissolution of metal impurities. It does not require the use of a large amount of strong acid and high-temperature reaction. Therefore, the process is green, environmentally friendly and low-cost.

[0021] Second, the electrochemical performance is excellent. The process uses sand grinding to promote the dissolution of metal impurities, and high-temperature carbonization further evaporates the chloride salt. The surface is coated with a high-purity carbon layer to further avoid the adverse effects of metal impurities and effectively reduce the specific surface area of ​​the hard carbon material, thereby achieving the purpose of improving the first-cycle efficiency and cycle performance of the hard carbon material.

[0022] Third, the processing performance is good. The invention can make the pH of the hard carbon material neutral, and in the slurry process of electrode production, it can avoid the deterioration of the slurry's fluidity due to the alkalinity of the material. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0024] The present invention discloses a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Pre-carbonization: pre-carbonizing the biomass raw material under a protective atmosphere to obtain a pre-carbonized material; S2, particle size control processing: crushing and refining the pre-carbonized material obtained in step S1 to obtain refined pre-carbonized material; S3, preparation of precursor material: the refined pre-carbonized material obtained in step S2, acid solution and deionized water are stirred and dispersed to form a precursor slurry, and the solid-liquid separation, water washing and drying are performed after temperature-controlled sand milling to obtain a precursor material; the acid solution is hydrochloric acid; the amount of the acid solution added is 1-20wt.% of the mass of the pre-carbonized material, the pH of the precursor slurry is 4-6; the solid content of the precursor slurry is 15-30%; S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under a protective atmosphere to obtain a purified hard carbon material; S5, high temperature carbon coating: the surface of the purified hard carbon material obtained in step S4 is subjected to high temperature carbon coating to obtain a surface-coated hard carbon negative electrode material.

[0025] Furthermore, in step S3, the sand grinding temperature is 30-80°C, the sand grinding time is 1-6h, and the D50 of the precursor material is ground to 3-10 μm.

[0026] Further, in step S3, the precursor material is washed with water until the pH value is 6-7; the solid-liquid separation method is centrifugation and / or filter pressing; the drying method is one or more of blast oven drying, flash drying, vacuum oven drying, tunnel drying furnace, double cone dryer, belt dryer, and rake dryer.

[0027] Furthermore, in step S5, the high-temperature carbon coating method is one or more of chemical vapor deposition, liquid phase coating and high-temperature solid phase coating; the raw material of the high-temperature carbon coating is a carbon source free of metal impurities, and the carbon source is one or more of asphalt, phenolic resin, PVP, PVA, dopamine, glucose, PAA, citric acid, phenol, benzene, toluene, and acetylene.

[0028] Further, in step S5, the amount of the carbon layer in the high-temperature coated carbon is 0.5-5wt.% of the weight of the hard carbon material; the heating rate is 1-10°C / min, the carbonization temperature is 600-1100°C, and the carbonization time is 1-3 h.

[0029] Furthermore, in step S4, the conditions for high temperature carbonization are: a heating rate of 0.5-10°C / min, a carbonization temperature of 1100-1500°C, and a carbonization time of 2-5 h.

[0030] Furthermore, in step S2, the pre-carbonized material is pulverized to a D50 of 5-20 μm, and the pulverization method is one or more of jaw crusher, roller crusher, air flow mill, mechanical mill, ball mill, Raymond mill, and stirred mill.

[0031] Furthermore, in step S1, the carbonization conditions are: a heating rate of 1-20°C / min, a carbonization temperature of 300-900°C, and a carbonization time of 1-5 h.

[0032] Furthermore, in step S1, the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal.

[0033] Further, in steps S1 / S4 and S5, the protective atmosphere is nitrogen and / or argon.

[0034] Example 1 This embodiment relates to a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Pre-carbonization: pre-carbonize the biomass raw materials under a protective atmosphere to obtain pre-carbonized materials. Specifically, the carbonization conditions are: heating rate of 20 °C / min, carbonization temperature of 600 °C, and carbonization time of 1 h. The biomass raw materials are walnut shells, nut shells, apricot shells, straw, and reeds.

[0035] S2, particle size control treatment: the pre-carbonized material obtained in step S1 is crushed and refined to obtain refined pre-carbonized material. Specifically, the pre-carbonized material is crushed and refined to a D50 of 5-20 μm, the crushing method is jaw crusher and roller, and the protective atmosphere is nitrogen.

[0036] S3, preparation of precursor material: stir and disperse the refined pre-carbonized material, acid solution and deionized water obtained in step S2 to form a precursor slurry, and perform solid-liquid separation, water washing and drying after temperature-controlled sand milling to obtain the precursor material; the acid solution is hydrochloric acid; the amount of acid solution added is 20wt.% of the mass of the pre-carbonized material, the pH of the precursor slurry is 5; the solid content of the precursor slurry is 15%. Specifically, the sand milling temperature is 80°C, the sand milling time is 3h, and the D50 of the precursor material is ground to 3-10μm; the precursor material is washed with water until the pH of the precursor material is 6; the solid-liquid separation method is centrifugation; the drying method is forced air oven drying.

[0037] S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under a protective atmosphere to obtain a purified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 0.5°C / min, a carbonization temperature of 1500°C, a carbonization time of 4 hours, and a protective atmosphere of nitrogen.

[0038] S5, high temperature carbon coating: The surface of the purified hard carbon material obtained in step S4 is subjected to high temperature carbon coating to obtain a surface-coated hard carbon negative electrode material. Specifically, the high temperature carbon coating is carried out by chemical vapor deposition; the raw material of the high temperature carbon coating is a carbon source free of metal impurities, and the carbon source is asphalt and phenolic resin; the amount of the carbon layer in the high temperature coated carbon is 0.5wt.% of the weight of the hard carbon material; the heating rate is 10 ℃ / min, the carbonization temperature is 800 ℃, and the carbonization time is 1 h; the protective atmosphere is nitrogen.

[0039] Example 2 This embodiment relates to a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Pre-carbonization: pre-carbonize the biomass raw material under a protective atmosphere to obtain a pre-carbonized material. Specifically, the carbonization conditions are: a heating rate of 10°C / min, a carbonization temperature of 300°C, and a carbonization time of 5 hours. The biomass raw materials are walnut shells, nut shells, anthracite, lignite, and sub-bituminous coal.

[0040] S2, particle size control treatment: the pre-carbonized material obtained in step S1 is crushed and refined to obtain refined pre-carbonized material. Specifically, the pre-carbonized material is crushed and refined to a D50 of 5-20 μm, the crushing method is Raymond mill, stirring mill, and the protective atmosphere is argon.

[0041] S3, preparation of precursor material: stir and disperse the refined pre-carbonized material, acid solution and deionized water obtained in step S2 to form a precursor slurry, and perform solid-liquid separation, water washing and drying after temperature-controlled sand milling to obtain the precursor material; the acid solution is hydrochloric acid; the amount of acid solution added is 10wt.% of the mass of the pre-carbonized material, the pH of the precursor slurry is 4; the solid content of the precursor slurry is 30%. Specifically, the sand milling temperature is 60°C, the sand milling time is 1h, and the D50 of the precursor material is ground to 3-10μm; the precursor material is washed with water until the pH of the precursor material is 7; the solid-liquid separation method is filter press; the drying method is forced air oven drying and flash drying.

[0042] S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under a protective atmosphere to obtain a purified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 5°C / min, a carbonization temperature of 1100°C, a carbonization time of 5 h, and an argon protective atmosphere.

[0043] S5, high temperature carbon coating: The surface of the purified hard carbon material obtained in step S4 is subjected to high temperature carbon coating to obtain a surface-coated hard carbon negative electrode material. Specifically, the high temperature carbon coating is carried out by chemical vapor deposition, liquid phase coating and high temperature solid phase coating; the raw material of the high temperature carbon coating is a carbon source free of metal impurities, and the carbon source is dopamine, glucose, and PAA; the amount of the carbon layer in the high temperature coated carbon is 2wt.% of the weight of the hard carbon material; the heating rate is 1 ℃ / min, the carbonization temperature is 1100 ℃, and the carbonization time is 2h; the protective atmosphere is argon.

[0044] Example 3 This embodiment relates to a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Pre-carbonization: pre-carbonize the biomass raw material under a protective atmosphere to obtain a pre-carbonized material. Specifically, the carbonization conditions are: a heating rate of 1 °C / min, a carbonization temperature of 900 °C, and a carbonization time of 3 h. The biomass raw materials are walnut shells, nut shells, apricot shells, straw, anthracite, lignite, and sub-bituminous coal.

[0045] S2, particle size control treatment: the pre-carbonized material obtained in step S1 is crushed and refined to obtain refined pre-carbonized material. Specifically, the pre-carbonized material is crushed and refined to a D50 of 5-20 μm, the crushing method is air flow powder, mechanical grinding, and the protective atmosphere is nitrogen and argon.

[0046] S3, preparation of precursor material: stir and disperse the refined pre-carbonized material, acid solution and deionized water obtained in step S2 to form a precursor slurry, and perform solid-liquid separation, water washing and drying after temperature-controlled sand milling to obtain the precursor material; the acid solution is hydrochloric acid; the amount of acid solution added is 1wt.% of the mass of the pre-carbonized material, the pH of the precursor slurry is 6; the solid content of the precursor slurry is 23%. Specifically, the sand milling temperature is 30°C, the sand milling time is 6h, and the D50 of the precursor material is ground to 3-10μm; the precursor material is washed with water until the pH of the precursor material is 6.5; the solid-liquid separation method is centrifugation and / or filter pressing; the drying method is vacuum oven drying or tunnel drying furnace.

[0047] S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under a protective atmosphere to obtain a purified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 0.5°C / min, a carbonization temperature of 1500°C, a carbonization time of 3 h; and the protective atmosphere is nitrogen and argon.

[0048] S5, high temperature carbon coating: The surface of the purified hard carbon material obtained in step S4 is subjected to high temperature carbon coating to obtain a surface-coated hard carbon negative electrode material. Specifically, the high temperature carbon coating is carried out by chemical vapor deposition, liquid phase coating and high temperature solid phase coating; the raw material of the high temperature carbon coating is a carbon source free of metal impurities, and the carbon source is PAA, citric acid, phenol, benzene, toluene, acetylene; the amount of the carbon layer in the high temperature coated carbon is 0.5wt.% of the weight of the hard carbon material; the heating rate is 10 ℃ / min, the carbonization temperature is 900 ℃, and the carbonization time is 1h; the protective atmosphere is nitrogen and argon.

[0049] Example 4 This embodiment relates to a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Pre-carbonization: pre-carbonize the biomass raw material under a protective atmosphere to obtain a pre-carbonized material. Specifically, the carbonization conditions are: a heating rate of 5 °C / min, a carbonization temperature of 700 °C, and a carbonization time of 2 h. The biomass raw materials are reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, and fir.

[0050] S2, particle size control treatment: the pre-carbonized material obtained in step S1 is crushed and refined to obtain refined pre-carbonized material. Specifically, the pre-carbonized material is crushed and refined to a D50 of 5-20 μm, the crushing method is jaw crusher, roller, stirring mill; the protective atmosphere is nitrogen and argon.

[0051] S3, preparation of precursor material: stir and disperse the refined pre-carbonized material, acid solution and deionized water obtained in step S2 to form a precursor slurry, and perform solid-liquid separation, water washing and drying after temperature-controlled sand milling to obtain the precursor material; the acid solution is hydrochloric acid; the amount of acid solution added is 5wt.% of the mass of the pre-carbonized material, the pH of the precursor slurry is 5; the solid content of the precursor slurry is 20%. Specifically, the sand milling temperature is 70°C, the sand milling time is 2h, and the D50 of the precursor material is ground to 3-10μm; the precursor material is washed with water until the pH of the precursor material is 6; the solid-liquid separation method is centrifugation and / or filter pressing; the drying method is flash drying or rake dryer.

[0052] S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under a protective atmosphere to obtain a purified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 3 °C / min, a carbonization temperature of 1300 °C, a carbonization time of 4 h; and the protective atmosphere is nitrogen and argon.

[0053] S5, high temperature carbon coating: The surface of the purified hard carbon material obtained in step S4 is subjected to high temperature carbon coating to obtain a surface-coated hard carbon negative electrode material. Specifically, the high temperature carbon coating is carried out by chemical vapor deposition, liquid phase coating and high temperature solid phase coating; the raw material of the high temperature carbon coating is a carbon source free of metal impurities, and the carbon source is asphalt, phenolic resin, PVP, PVA, dopamine, glucose; the amount of the carbon layer in the high temperature coated carbon is 4wt.% of the weight of the hard carbon material; the heating rate is 3℃ / min, the carbonization temperature is 700℃, and the carbonization time is 1.5h; the protective atmosphere is nitrogen and argon.

[0054] Example 5 This embodiment relates to a green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Pre-carbonization: pre-carbonize the biomass raw material under a protective atmosphere to obtain a pre-carbonized material. Specifically, the carbonization conditions are: a heating rate of 15 °C / min, a carbonization temperature of 400 °C, and a carbonization time of 4 hours. The biomass raw materials are walnut shells, nut shells, apricot shells, and straw.

[0055] S2, particle size control treatment: the pre-carbonized material obtained in step S1 is crushed and refined to obtain refined pre-carbonized material. Specifically, the pre-carbonized material is crushed and refined to a D50 of 5-20 μm, the crushing method is jaw crushing, and the protective atmosphere is nitrogen and argon.

[0056] S3, preparation of precursor material: stir and disperse the refined pre-carbonized material, acid solution and deionized water obtained in step S2 to form a precursor slurry, and perform solid-liquid separation, water washing and drying after temperature-controlled sand milling to obtain the precursor material; the acid solution is hydrochloric acid; the amount of acid solution added is 15wt.% of the mass of the pre-carbonized material, the pH of the precursor slurry is 4; the solid content of the precursor slurry is 20%. Specifically, the sand milling temperature is 60°C, the sand milling time is 4h, and the D50 of the precursor material is ground to 3-10μm; the precursor material is washed with water until the pH of the precursor material is 6; the solid-liquid separation method is centrifugation and / or filter pressing; the drying method is a drum dryer or a rake dryer.

[0057] S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under a protective atmosphere to obtain a purified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 3 °C / min, a carbonization temperature of 1400 °C, a carbonization time of 4 h; and the protective atmosphere is nitrogen and argon.

[0058] S5, high temperature carbon coating: The surface of the purified hard carbon material obtained in step S4 is subjected to high temperature carbon coating to obtain a surface-coated hard carbon negative electrode material. Specifically, the high temperature carbon coating is carried out by chemical vapor deposition, liquid phase coating and high temperature solid phase coating; the raw material of the high temperature carbon coating is a carbon source free of metal impurities, and the carbon source is glucose, PAA, citric acid, phenol, benzene, toluene, acetylene; the amount of the carbon layer in the high temperature coated carbon is 4wt.% of the weight of the hard carbon material; the heating rate is 3℃ / min, the carbonization temperature is 1000℃, and the carbonization time is 2h; the protective atmosphere is nitrogen and argon.

[0059] Application Example 1 This embodiment relates to a hard carbon negative electrode material for an ion battery. The preparation process thereof includes the following steps: S1. Pre-carbonization: pre-carbonize the coconut shell raw material in a nitrogen atmosphere at a heating rate of 5 °C / min, a carbonization temperature of 700 °C, and a carbonization time of 3 to obtain a pre-carbonized material.

[0060] S2. Particle size control treatment: The pre-carbonized material obtained in step S1 is crushed and refined using a double-roll mill and a mechanical mill to obtain a pre-carbonized material with D50=10 μm.

[0061] S3, preparation of precursor material: stir and disperse the crushed pre-carbonized material, acid solution and deionized water obtained in step S2 in a dispersion tank to obtain a precursor slurry, wherein the amount of hydrochloric acid added is 10 wt.% of the amount of pre-carbonized material added, the pH of the slurry is 4.5; the solid content of the slurry is 25%. Then sand milling is performed: the sand milling temperature is 60°C, the time is 1.5, and the D50 of the material is ground to 5μm. Then centrifuge, wash with water to pH=6, and dry in a blast oven to obtain the precursor material.

[0062] S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under nitrogen gas, with a heating rate of 2 °C / min, a carbonization temperature of 1400 °C, and a carbonization time of 3 h to obtain a purified hard carbon material; S5. High-temperature carbon coating: acetylene is used as a coating agent and the coating is carried out by CVD. The coating atmosphere is argon gas. The coating temperature is 800°C and the deposition time is 1 hour to obtain a surface-coated hard carbon negative electrode material.

[0063] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a homogenous slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on the copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, and metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) was used as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0064] Comparative Example 1 (without sanding) This embodiment relates to a hard carbon negative electrode material for an ion battery. The preparation process thereof includes the following steps: S1. Pre-carbonization: pre-carbonize the coconut shell raw material in a nitrogen atmosphere at a heating rate of 5 °C / min, a carbonization temperature of 700 °C, and a carbonization time of 3 to obtain a pre-carbonized material.

[0065] S2. Fineness control treatment: Use a double roller mill and a mechanical mill to crush and refine the pre-carbonized material obtained in step S1 to obtain a pre-carbonized material with D50=5 μm.

[0066] S3, high temperature sintering: the precursor material obtained in step S2 is subjected to high temperature carbonization under nitrogen gas, the heating rate is 2 ° C / min, the carbonization temperature is 1400 ° C, and the carbonization time is 3 hours to obtain a purified hard carbon material; S4. High-temperature carbon coating: Acetylene is used as a coating agent and the coating is carried out by CVD. The coating atmosphere is argon gas. The coating temperature is 800°C and the deposition time is 1 hour to obtain a surface-coated hard carbon negative electrode material.

[0067] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a homogenous slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on the copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, and metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) was used as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0068] Comparative Example 2 (without coating) This embodiment relates to a hard carbon negative electrode material for an ion battery. The preparation process thereof includes the following steps: S1. Pre-carbonization: pre-carbonize the coconut shell raw material in a nitrogen atmosphere at a heating rate of 5 °C / min, a carbonization temperature of 700 °C, and a carbonization time of 3 to obtain a pre-carbonized material.

[0069] S2. Fineness control treatment: Use a roller mill and a mechanical mill to crush and refine the pre-carbonized material obtained in step S1 to obtain a pre-carbonized material with D50=10 μm.

[0070] S3, preparation of precursor material: stir and disperse the crushed pre-carbonized material, acid solution and deionized water obtained in step S2 in a dispersion tank, wherein the amount of hydrochloric acid added is 10 wt.% of the amount of pre-carbonized material added, the pH of the slurry is 4.5; the solid content of the slurry is 25%. Then sand milling is performed: the sand milling temperature is 60°C, the time is 1.5, and the D50 of the material is ground to 5μm. Then centrifuge, wash with water to pH=6, and dry in a blast oven to obtain the precursor material.

[0071] S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under nitrogen gas, with a heating rate of 2 °C / min, a carbonization temperature of 1400 °C, and a carbonization time of 3 h to obtain a purified hard carbon material; The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a homogenous slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on the copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, and metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) was used as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0072] The ash content of Example 1, Comparative Example 1 and Comparative Example 2 was 0.6%, 2.5% and 0.7% respectively, indicating that the sand grinding and acid addition process can significantly reduce the content of impurities in the hard carbon material.

[0073] The pH test results show that the pH of Example 1, Comparative Example 1 and Comparative Example 2 are 7.5, 10.6 and 8.1 respectively, indicating that the sand grinding, acid addition and surface coating process can effectively reduce the pH of the hard carbon material, thereby improving the processability of the material.

[0074] The nitrogen adsorption and desorption test results show that the specific surface areas of Example 1, Comparative Example 1 and Comparative Example 2 are 4.3, 5.3 and 10.6 m, respectively. 2 / g, indicating that the surface coating process can effectively reduce the specific surface area of ​​the material.

[0075] The constant current charge and discharge test showed that the first-week charging specific capacities of Example 1, Comparative Example 1 and Comparative Example 2 were 301, 290 and 287 mAh / g, respectively, and the first-week coulombic efficiencies were 92.3, 91.1 and 87.4%, respectively, indicating that increasing the purity of the hard carbon material and reducing the surface area of ​​the material can effectively improve the weekly coulombic efficiency of the hard carbon material.

[0076] The constant current charge and discharge test showed that the capacity retention rates of Example 1, Comparative Example 1 and Comparative Example 2 after 200 cycles were 89.4, 82.3 and 79.4%, respectively, indicating that the sand grinding, acid addition and surface coating process can effectively improve the cycle performance of hard carbon materials.

[0077] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A green and environmentally friendly method for preparing a hard carbon negative electrode material for a sodium ion battery, characterized in that The following steps are involved: S1. Pre-carbonization: pre-carbonizing the biomass raw material under a protective atmosphere to obtain a pre-carbonized material; S2, particle size control processing: crushing and refining the pre-carbonized material obtained in step S1 to obtain refined pre-carbonized material; S3, preparation of precursor material: the refined pre-carbonized material obtained in step S2, acid solution and deionized water are stirred and dispersed to form a precursor slurry, and the precursor material is obtained by temperature-controlled sand milling, solid-liquid separation, water washing and drying. The acid solution is hydrochloric acid; the amount of the acid solution added is 1-20wt.% of the mass of the pre-carbonized material, the pH of the precursor slurry is 4-6; the solid content of the precursor slurry is 15-30%; S4, high temperature sintering: the precursor material obtained in step S3 is subjected to high temperature carbonization under a protective atmosphere to obtain a purified hard carbon material; S5, high temperature carbon coating: the surface of the purified hard carbon material obtained in step S4 is subjected to high temperature carbon coating to obtain a surface-coated hard carbon negative electrode material.

2. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step S3, the sand grinding temperature is 30-80°C, the sand grinding time is 1-6 hours, and the D50 of the precursor material is ground to 3-10 μm.

3. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step S3, the precursor material is washed with water until the pH value is 6-7; the solid-liquid separation method is centrifugation and / or filter pressing; the drying method is one or more of blast oven drying, flash drying, vacuum oven drying, tunnel drying furnace, double cone dryer, belt dryer, and rake dryer.

4. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step S5, the high-temperature carbon coating method is one or more of chemical vapor deposition, liquid phase coating and high-temperature solid phase coating; the raw material of the high-temperature carbon coating is a carbon source free of metal impurities, and the carbon source is one or more of asphalt, phenolic resin, PVP, PVA, dopamine, glucose, PAA, citric acid, phenol, benzene, toluene, and acetylene.

5. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step S5, the amount of the carbon layer in the high-temperature coated carbon is 0.5-5wt.% of the weight of the hard carbon material; the heating rate is 1-10°C / min, the carbonization temperature is 600-1100°C, and the carbonization time is 1-3 h.

6. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step S4, the high temperature carbonization conditions are: heating rate of 0.5-10°C / min, carbonization temperature of 1100-1500°C, and carbonization time of 2-5 h.

7. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step S2, the pre-carbonized material is pulverized to a D50 of 5-20 μm by one or more of the following methods: jaw crusher, roller crusher, air flow mill, mechanical mill, ball mill, Raymond mill, and stirred mill.

8. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 7, characterized in that: In step S1, the carbonization conditions are: heating rate of 1-20°C / min, carbonization temperature of 300-900°C, and carbonization time of 1-5 h.

9. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 8, characterized in that: In step S1, the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal.

10. The method for preparing a green and environmentally friendly hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In steps S1 / S4 and S5, the protective atmosphere is nitrogen and / or argon.

Citation Information

Patent Citations

  • Method for purifying and preparing silicon carbide powder from crystalline silicon cutting waste mortar

    CN103359736A

  • Method for removing metal impurities from carbon nano tube

    CN104211042A

  • Green preparation method of nitrogen-boron codoped biomass-based activated carbon material and application thereof

    CN110422843A

  • Environment-friendly high-cycling-stability biomass hard carbon negative electrode material for sodium-ion battery and preparation method of green environment-friendly high-cycling-stability biomass hard carbon negative electrode material

    CN117509609A

  • Hard carbon negative electrode material of fast-charging sodium-ion battery and preparation method of hard carbon negative electrode material

    CN118771356A

Cited By

  • Coconut shell biomass hard carbon material for negative electrode of sodium ion battery and preparation method of coconut shell biomass hard carbon material

    CN119612497A

  • Sodium-ion battery hard carbon negative electrode material and preparation method and application thereof

    CN120964770A